Development of the Altruism Scale for Children: An Assessment of Caring Behaviors Among Children. (2nd January 2020) - Swank, Jacqueline M.; Limberg, Dodie; Liu, Ren
Abstract: This article focuses on the development of the Altruism Scale for Children (ASC). Analyses revealed a one-factor model with internal consistency of 0.89 and test-retest reliability of 0.94. The authors also discuss the implications for using the instrument for assessing the need for interventions and measuring program outcomes.